2004
DOI: 10.1590/s0037-86822004000600015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Zymomonas mobilis culture on experimental Schistosoma mansoni infection

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 6 publications
2
8
0
1
Order By: Relevance
“…These results are similar to the study of Mohamed et al (29) and Zowail et al (30) who proved the protective and curative effects of useful bacteria in mice models against infection of Schistosoma mansoni (29)(30)(31). Many strains of probiotics, like Zymomonas mobilis 1*10 9 CFU/ml, when administrated by mouth provoked minor defense reaction, in mice against S. mansoni by providing prevention in treated animals (31,32). When Lactobacillus sporogenes used orally at a certain dose, for a long time,since the beginning of the infestation with S. mansoni, minimized impairment of DNA, improves liver and gut deterioration, therefore weakened adult together with ova numbers (29).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are similar to the study of Mohamed et al (29) and Zowail et al (30) who proved the protective and curative effects of useful bacteria in mice models against infection of Schistosoma mansoni (29)(30)(31). Many strains of probiotics, like Zymomonas mobilis 1*10 9 CFU/ml, when administrated by mouth provoked minor defense reaction, in mice against S. mansoni by providing prevention in treated animals (31,32). When Lactobacillus sporogenes used orally at a certain dose, for a long time,since the beginning of the infestation with S. mansoni, minimized impairment of DNA, improves liver and gut deterioration, therefore weakened adult together with ova numbers (29).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, bacterial output holds anthelmintic influence that might decrease maliciousness of numerous protozoa and helminthic illness (28). These results are similar to the study of Mohamed et al (29) and Zowail et al (30) who proved the protective and curative effects of useful bacteria in mice models against infection of Schistosoma mansoni (29)(30)(31). Many strains of probiotics, like Zymomonas mobilis 1*10 9 CFU/ml, when administrated by mouth provoked minor defense reaction, in mice against S. mansoni by providing prevention in treated animals (31,32).…”
Section: Discussionsupporting
confidence: 75%
“…Probiotics, including species of Lactobacillus and Bifidobacterium (Butel, 2014 ), are thought to protect against infection by competing with pathogens for space and resources, modulating the host immune system, and producing antimicrobial peptides (Corr et al, 2009 ). Although studies investigating the effects of probiotics on helminth infections have yielded conflicting results, with studies showing that probiotics can reduce helminth burdens (Stefanski and Przyjalkowski, 1965 , 1966 ; Bautista-Garfias et al, 1999 , 2001 ; Santos et al, 2004 ; Basualdo et al, 2007 ; Martínez-Gómez et al, 2009 , 2011 ; Chiodo et al, 2010 ; Oliveira-Sequeira et al, 2014 ), increase susceptibility to helminths (Dea-Ayuela et al, 2008 ; Reynolds et al, 2014 ), or have no effect on helminth burden (de Waard et al, 2001 ; Verdú et al, 2004 ), the majority of published studies have found a decrease in helminth burdens with probiotic administration. This suggests that certain probiotic species may help protect against helminth infection, though the underlying mechanisms remain unclear.…”
Section: Applications Of Understanding Parasite-microbiota Interactiomentioning
confidence: 99%
“…Also Enterococcus faecalis CECT7121, a probiotic with inhibitory activity against Gram-positive and Gram-negative bacteria, possesses in vitro and in vivo larvicidal activity determining up to a 90% reduction of the number of Toxocara canis larvae in liver and lungs of laboratory mice (Basualdo et al, 2007; Chiodo et al, 2010). Zymomonas mobilis , a bacterium producer of bioethanol, was reported to provide over 60% protection from the infection of S. mansoni in mice (Santos Jde et al, 2004). …”
Section: Probiotics Against Parasitesmentioning
confidence: 99%